History of the entomology chairs at the Universidad Centroccidental “Lisandro Alvarado” (Revista Electrónica REDINE, 2025)
This document describes the teaching, research, daytime and nighttime insect collections, and the development of the Museum of Entomology (MJMO) carried out by Dr. José Manuel Osorio Rojas and the professional staff of the Entomology Chairs, School of Agronomy, UCLA. The Chairs of Entomology and the MJMO were founded by Dr. Osorio on July 1, 1965, at the Centro Experimental de Estudios Superiores (CEDES). During his tenure at CEDES (1965-1966), Dr. Osorio made the first daytime insect collections for teaching purposes and for the Museum's insect collection. During the fifth semester (January-June 1966), he taught the first Systematic Entomology course. The School of Agronomy was subsequently relocated to the western part of Barquisimeto, where Dr. Osorio taught the Economic Entomology course for the first time during the sixth semester (July–December 1966). Beginning in 1969, as professional staff joined the chairs, in addition to teaching, research projects were developed and insect collections continued. In December 1990, the Entomology Chairs were relocated to Tarabana, Palavecino Municipality, Lara State, where teaching, research projects, and insect collections continued. Regarding the professional activity of Dr. José Manuel Osorio Rojas in the History of Entomology, from CEDES to UCLA, during thirty-three years as a University Professor, it is important to highlight his scientific legacy, which contributed significantly to the training of excellent Professionals in Agricultural Engineering, with both national and international recognition, and to the prestige of our Institution, UCLA. The scientific activities of Dr. José Manuel Osorio Rojas extended until 1998, when he had to travel to Madrid, Spain, for family reasons.
Keywords: CEDES; chairs of Entomology; museum; insect collecting; UCLA